Pensamiento en los estados ansiógenos - Sarango Pogo, Sara Janneth (Machala : Universidad Técnica de Machala., 2015)
La presente investigación tiene como objetivo analizar los procesos del pensamiento en los estados ansiógenos, se selecciona el enfoque cognitivo conductual con la finalidad de fundamentar el análisis del caso. Se investiga dos variables importantes en los procesos cognitivos de los estados ansiógenos, las distorsiones cognitivas (pensamientos automáticos negativos) y las creencias irracionales.
This research aims to analyze the thought processes in the states of anxiety, for its realization, it took information addressed by the cognitive behavioral approach based on the theory of Albert Ellis, who contributes significantly in the field of psychological symptoms of anxiety. It explores two important variables in the cognitive processes of the states of anxiety, the cognitive distortions (automatic negative thoughts) and the irrational beliefs.
Keywords: PENSAMIENTO; ESTADO ANSIOGENO; PSICOLOGIA; CLINICA